摆动活齿传动重合度分析 - 张华弟; 王保平 (Jixie chuandong)
In this paper, a new model and method are presented to calculate the Overlap ration of oscillator drives. Using this method, the formula has been deduced and the Overlap ration of oscillator drives has been obtained. The effect of the structure parameter error on overlap ration of oscillator drives is also given.